PERBEDAAN TINGKAT STRES KERJA PERAWAT RUANG INTENSIF DAN NON INTENSIF : LITERATUR REVIEW - FITRI ESI OKTA WULANSARI; Safri Safri; Widia Lestari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Nurses as a professional worker in the hospital are vulnerable of getting stress that causes physiologies, psychologies, and behavior disorder. The purpose of this study is to analyze and to review the differences working stress level of the nurses in intensive and non-intensive room. Literature review method is used in this study. The sources of the data are articles in data base used google scholar and science direct with “working stress”, “intensive nurse” or “emergency nurse”, and “patient ward” or “non-intensive nurse” as key words. There are in total 1.142 articles. 10 articles were obtained after filtered using inclusion criteria in period 2015 to 2020. The result of working stress level of the nurses in intensive room is mostly in middle level, and the working stress level of the nurses in non-intensive room is zero. It can be concluded that there are differences working stress level of the nurses in intensive and non-intensive room. It is recommended that the nurses should have stress managing so that they are able to give better service to the patients quickly and effectively.Keywords: nurse, working stress